Current State of Cholera Specific Prophylaxis - I. A. Bespalova; I. A. Ivanova; N. D. Omelchenko; A. V. Filippenko; A. A. Trufanova (Эпидемиология и вакцинопрофилактика, 2018)
The threat of cholera spread beyond the borders of endemic countries and the realness of the emergence of introduced epidemic foci remain the actual problems and neccessitate continuous development of specific prophylaxis of this disease. The review is dedicated to the analysis of the effectiveness of licensed cholera vaccines as well as to possible perspectives of the advancement of cholera specific prophylaxis.